UZBEK THEATER AND CINEMA AS A WEAPON OF IDEOLOGICAL PROPAGANDA IN 20-50-IES OF XX CENTURY (Scientific journal of the Fergana State University, 2023)
In the article, the impact of "Cultural Revolution" policy, which was carried out during the reign of the former Soviet power, on the sphere of cinema and theater, the policy of the Soviet state on the ideology of culture and its manifestation in the national culture of its actions towards its implementation, the introduction of the personnel training system for the cinema and theater industry by the Soviet ideology was studied.